2007
DOI: 10.3184/030823407x207086
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of 4-phenyl-6-[(Z)phenylimino]-3,6-dihydro-1,3,5-thiadiazine-2,2-dicarbonitriles

Abstract: N-Imidoylthioureas 2a-e reacted with 1,1,2,2-tetracyanoethylene (1) to form the thiadiazines 3a-e. In the case of 1e, tricyanovinylation of a phenyl substituent accompanied formation of the thiadiazine ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Presumably, the CT complexes are transient intermediates. Thus, treatment of compounds 117a , 117b , 117c , 117d , 117e with 2 , under the conditions just described, afforded 1,3,5‐thiadiazines 118a , 118b , 118c , 118d , 118e in 85–68% yields (Scheme ) .…”
Section: Reaction Of Nonheterocylic Nucleophilic Donors With Acceptormentioning
confidence: 96%
See 1 more Smart Citation
“…Presumably, the CT complexes are transient intermediates. Thus, treatment of compounds 117a , 117b , 117c , 117d , 117e with 2 , under the conditions just described, afforded 1,3,5‐thiadiazines 118a , 118b , 118c , 118d , 118e in 85–68% yields (Scheme ) .…”
Section: Reaction Of Nonheterocylic Nucleophilic Donors With Acceptormentioning
confidence: 96%
“…Aly et al . reported that addition of 117a , 117b , 117c , 117d , 117e as electron donors to electron acceptor 2 in dichloromethane at r.t. led to complex formation characterized by CT bands in the visible region . These CT complexes gradually disappeared to give the precipitated reaction products.…”
Section: Reaction Of Nonheterocylic Nucleophilic Donors With Acceptormentioning
confidence: 99%
“…have recently reported a facile synthesis of thiazolidines through one‐pot three‐component reaction of equimolar amounts of thiosemicarbazones, arylidene malononitriles, and diethyl acetylenedicarboxylate under prolonged reflux in acetic acid . It was also reported that N ‐substituted hydrazino‐carbothioamides reacted with dibenzoylacetylene to give thiazine‐hydrazides , and that N ‐imidoylthioureas reacted with 1,1,2,2‐tetracyanoethylene to give thiadiazines . 2‐Amino‐1,1,2‐ethenetricarbonitrile ( 3 ) has recently been synthesized .…”
Section: Introductionmentioning
confidence: 99%
“…The formation of thiadiazine derivatives was observed during ammonolysis of isothiocyanate 53 as a result of intramolecular aminoalkylation and subsequent transformations of the intermediate thiourea 54 (Scheme 21). 102Heterocyclization of N-imidoylthioureas 55 in the presence of tetracyanoethylene gave the thiadiazines 56 103. The reaction apparently occurred via the intermediate 57, which underwent intramolecular N-alkylation with the elimination of malononitrile.…”
mentioning
confidence: 97%